The theoretical basis of crime prevention - Однолько, Інна Валентинівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
This paper considered issues relating to various approaches to understanding of the crime prevention. The author studied various scientific points of view, structured system of prevention measures. The author proposedher own approach to the feasibility of using the term «prevention». In the paper also was proposedauthor’s definition of the term «crime prevention».